Students' Perceptions of The Development of Digital Learning Platforms In Supporting The Learning Process - Sinaga, Andromeda Valentino (Jompa Research and Development, 2025)
This study explores students' views on how digital learning platforms support their learning process. Data were collected through a Likert-scale survey consisting of 10 items, using a 5-point scale ranging from Strongly Disagree to Strongly Agree. The survey was administered to 50 seventh-semester students at Universitas Negeri Makassar, selected purposively due to their extensive experience with online and blended learning. Descriptive analysis was used to calculate mean scores and frequency distributions. Over 80% of respondents reported that digital platforms were particularly helpful in accessing learning materials and communicating with lecturers. Perception scores ranged from 3.8 to 4.4, with ease of accessing resources scoring the highest. In contrast, motivation received the lowest score, suggesting that technology alone may not sufficiently drive student engagement. These findings emphasize the need to optimize both digital platforms and pedagogical strategies to sustain motivation and foster deeper learning. The results imply that higher education institutions should integrate more student-centered and interactive approaches within digital environments.